(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2019)
This paper explores Sufi method of being enlightened through deep reflection in reading a Persian travelogue written by ??jj Sayy?? entitled, Safarn?ma?-i ??jj Sayy?? bih Farang (SHS). After introducing the author and the travelogue background, this study presents the concepts of captivity awareness, knowledge and ignorance which become the basis of the journey in SHS. It then proceeds to the discussion on taming the soul through six ways; physical hardship, renunciation (zuhd), poverty, loneliness, illness and the experience of near death in order to escape the idiocy imprisonment. Finally, this paper explains the journey of freedom in SHS according to the framework of Sufi concepts about human conditions in an odyssey towards God. In conclusion, high level of captivity awareness enhances motivation to seek for an escape path from mind or conceptual captivity. Within the site of travel, the “purification” process of imprisoning the soul is enhanced and it provides a path towards the exceptional kind of liberation.